Borylated Oximes: Versatile Building Blocks for Organic Synthesis - Liew, Sean K. (Chem Commun (Camb), 2017)
Herein, we demonstrate the synthesis and functionalization of α-boryl aldoximes from α-boryl aldehydes, with no sign of c-to-n boryl migration. selective modification of the oxime functionality enables access to a wide range of borylated compounds, such as borylated heterocycles and N-acetoxyamides. by reducing the α-boryl aldoximes, mida deprotection yields the corresponding β-boryl hydroxylamines. as part of this study, we also demonstrate the utility of the boryl aldoxime motif in peptide conjugation.